Pengaruh Latihan Resistance Band Terhadap Kecepatan Tendangan Sabit Pada Perguruan Pencak Silat Cinde Wulung - Rahman, Aditya; Firdaus hendry; Goesti Sabda Laksana (Jurnal Ilmiah STOK Bina Guna Medan, 2025)
This study aims to determine the effect of resistance band training on the speed of the sabit kick in silat athletes at Perguruan Cinde Wulung. Kick speed is one of the important aspects in silat, especially in the competition category. The sabit kick is often used to score points in matches. The research method used is a quasi-experimental design with a one group pretest-posttest design. The sample in this study consists of 30 athletes selected randomly. The data collection instrument uses a sabit kick speed test measured through an application called Kinovea. This research was conducted over 16 meetings, consisting of 14 training sessions using resistance bands, one pretest, and one posttest. The results of the normality test processed using SPSS indicate that the data is normally distributed. The hypothesis test using paired samples T-test analysis shows a significant relationship between the pretest and posttest results with a correlation value of 0.898 and a significance of 0.000 (p < 0.05). These findings indicate that resistance band training significantly improves the speed of the sabit kick. Thus, resistance band training can be an effective method for enhancing kick speed in silat. This training is recommended to be implemented in routine training programs, both by coaches and silat athletes.